Distribution and abundances of diazotrophs and microbial nutrient limitations in the North Atlantic Ocean - Langlois-Warnat, Rebecca Judith (2008)
The diversity and abundances of diazotrophic organisms were determined in field samples from the Atlantic Ocean. A nested PCR technique, amplifiying the structural nifH gene of nitrogenase, and subsequent phylogenetic analysis was used to determine diazotroph diversity. The abundances of seven diazotrophic phylotypes were estimated by real-time PCR. TaqMan qPCR primers and probes were designed to target four cyanobacterial (one filamentous and three unicellular), two putative gamma-proteobacterial, and one putative anaerobic nifH phylotype(s). Over half of the total nifH copies detected were filamentous, indicating that this is an important diazotroph. The potential for diazotrophy above 30°N and at nitrate concentrations above 0.5 µM was demonstrated by the presence of nifH genes under these conditions. Results of nutrient addition bioassay experiments showed that nitrogen fixation was phosphorus and iron co-limited, however increases in nifH copy numbers was seen only with the addition of Saharan dust indicating that Saharan dust influences diazotroph distributions. A laboratory experiment conducted with Trichodesmium erythraeum demonstrated that this organism can utilize iron from Saharan dust. Bioassay experiments also revealed that primary production was nitrogen limited and heterotrophic bacterial production was nitrogen and phosphorus co-limited throughout the Northern Atlantic Ocean, emphasizing the important role diazotrophs have by providing fixed nitrogen in this system.